2016
DOI: 10.1007/978-3-319-27216-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania tarentolae for the Production of Multi-subunit Complexes

Abstract: Multi-subunit protein complexes are involved in a wide variety of cellular processes including DNA replication, transcriptional regulation, signal transduction, protein folding and degradation. A better understanding of the function of these protein complexes requires structural insights into the molecular arrangement and interactions of their constituent subunits. However, biochemical and structural analysis of multi-subunit protein complexes is still limited because of technical difficulties with their recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…L . tarentolae is a non-pathogenic parasite that does not cause pathology in humans nor in immunodeficient mice and its non-pathogenicity has been recently proven in several studies [ 55 , 64 , 65 ]. We showed here that injection of L .…”
Section: Discussionmentioning
confidence: 99%
“…L . tarentolae is a non-pathogenic parasite that does not cause pathology in humans nor in immunodeficient mice and its non-pathogenicity has been recently proven in several studies [ 55 , 64 , 65 ]. We showed here that injection of L .…”
Section: Discussionmentioning
confidence: 99%
“…However, functional expression results of single-chain fragment variables (scFv’s) [12] and scFv-fragment crystallizable (scFv-Fc) fusion proteins [13] indicate that successful expression of full-length antibodies is only a matter of time [130]. The successful expression of multisubunit proteins, like the human heterotrimeric glycoprotein LM-322 [17,131], further underpins the general capacity of L . tarentolae to express full-length antibodies, as they also consist of several subunits.…”
Section: Biotechnological Applications Of L Tarentolaementioning
confidence: 99%
“…The protozoan parasites of the genus Leishmania belong to the Trypanosomatidae family (one of the oldest groups of eukaryotes), which comprises unicellular organisms recognized by their single flagellum and a unique mitochondrial DNA-containing organelle, the kinetoplast ( Niimi, 2016 ). Due to its public health significance, the Trypanosomatidae group is one of the best-studied eukaryotic groups after yeast ( Basile and Peticca, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…L. tarentolae does not cause pathogenicity in humans and even in severe combined immunodeficient mice (Breton et al, 2005;Niimi, 2016). Recently, many studies on animals, such as mice, hamsters, and dogs have shown that the use of L. tarentolae can be a promising approach for vaccine development (as a live vector) against CL and VL (Saljoughian et al, 2013;Zahedifard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation